2021
DOI: 10.3847/1538-4357/abe0b8
|View full text |Cite
|
Sign up to set email alerts
|

[C ii] and CO Emission along the Bar and Counter-arms of NGC 7479*

Abstract: We present new SOFIA [C II] and ALMA CO J=1→0 observations of the nearby asymmetric barred spiral galaxy NGC 7479. The data, which cover the whole bar of the galaxy and the counter-arms visible in the radio continuum, are analyzed in conjunction with a wealth of existing visible, infrared, radio, and X-ray data. As in most normal galaxies, the [C II] emission is generally consistent with emission from cooling gas excited by photoelectric heating in photodissociation regions. However, anomalously high [C II]/CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In recent years, the consensus that [C II] has its origin in, and thus traces, star formation has been challenged by the discovery of [C II] formed from the interactions of AGN jets with the disk (Appleton et al 2018;Smirnova-Pinchukova et al 2019;Fadda et al 2021) and in galaxy-galaxy interactions (Appleton et al 2013(Appleton et al , 2017Peterson et al 2018). To these, as suggested by Pierini et al (1999), we can now add the interaction of galaxies with the cluster environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the consensus that [C II] has its origin in, and thus traces, star formation has been challenged by the discovery of [C II] formed from the interactions of AGN jets with the disk (Appleton et al 2018;Smirnova-Pinchukova et al 2019;Fadda et al 2021) and in galaxy-galaxy interactions (Appleton et al 2013(Appleton et al , 2017Peterson et al 2018). To these, as suggested by Pierini et al (1999), we can now add the interaction of galaxies with the cluster environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with the FIFI-LS instrument onboard the Stratospheric Observatory for Infrared Astronomy (SOFIA) have shown that turbulence in the interstellar medium (ISM) associated with interactions with jets can lead to the formation of [C II] distinct from starformation processes. As the infrared continuum also traces star formation (albeit only obscured star formation, while the [C II] can, in principle, reflect both the obscured star formation and the unobscured star formation traced by ultraviolet emission), and [C II] associated with star formation is excited via gas heated by the photoelectric effect of UV photons on small dust grains and polycyclic aromatic hydrocarbons (e.g., Herrera-Camus et al 2015), [C II] from other sources is identifiable as an excess in the [C II]/infrared continuum ratio, as seen in the host galaxies of active galactic nuclei (AGN) where the jet is interacting with the disk (Appleton et al 2018;Smirnova-Pinchukova et al 2019;Fadda et al 2021). Similarly, Herschel observations of gas in the collisionally formed bridge between the Taffy Galaxies (UGC 12914/ 12915) found enhanced [C II]/infrared continuum ratios that were attributed to turbulently heated H 2 and high columndensity H I resulting from the collision of the two galaxies (Peterson et al 2018), and models of warm molecular gas shocks in Stephan's Quintet point to collisional heating from the warm H 2 being responsible for boosting the [C II] emission in that system (Appleton et al 2013(Appleton et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the consensus that [C ii] has its origin in, and thus traces, star formation has been challenged by the discovery of [C ii] formed from the interactions of AGN jets with the disk (Appleton et al 2018;Smirnova-Pinchukova et al 2019;Fadda et al 2021) and in galaxygalaxy interactions (Appleton et al 2013(Appleton et al , 2017Peterson et al 2018). To these, as suggested by Pierini et al (1999), we can now add the interaction of galaxies with the cluster environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with the FIFI-LS instrument onboard the Stratospheric Observatory for Infrared Astronomy (SOFIA) have shown that turbulence in the interstellar medium (ISM) associated with interactions with jets can lead to the formation of [C ii] distinct from star formation processes. As the infrared continuum also traces star formation (albeit only obscured star formation, while the [C ii] can, in principle, reflect both the obscured star formation and the unobscured star formation traced by ultra-violet emission), and [C ii] associated with star formation is excited via gas heated by the photoelectric effect of UV photons on small dust grains and polycyclic aromatic hydrocarbons (e.g., Herrera-Camus et al 2015), [C ii] from other sources is identifiable as an excess in the [C ii]/infrared continuum ratio, as seen in the host galaxies of active galactic nuclei (AGN) where the jet is interacting with the disk Smirnova-Pinchukova et al 2019;Fadda et al 2021). Similarly, Herschel observations of gas in the collisionally-formed bridge between the Taffy Galaxies (UGC 12914/12915) found enhanced [C ii]/infrared continuum ratios that were attributed to turbulently heated H 2 and high column-density H i resulting from the collision of the two galaxies (Peterson et al 2018), and models of warm molecular gas shocks in Stephan's Quintet point to collisional heating from the warm H 2 being responsible for boosting the [C ii] emission in that system (Appleton et al 2013(Appleton et al , 2017.…”
Section: Introductionmentioning
confidence: 99%